1987
DOI: 10.1080/00926238708403890
|View full text |Cite
|
Sign up to set email alerts
|

Group treatment of secondary erectile dysfunction

Abstract: The effects of three group treatment formats on 20 men with secondary erectile dysfunction and their partners were contrasted. After a comprehensive medical and psychological screening, each couple was assigned to one of three treatment groups (Communication Technique Training, Sexual Technique Training, Combination Treatment) or to one of two control groups (Attention-Placebo, No-Treatment). Couples in the three treatment groups and the attention-placebo group participated in their respective formats in twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…Attrition from Rekindle was much higher than has been reported for face-to-face psychological treatments for sexual dysfunction, where discontinuation rates have been found to range from between 1.6% and 52.6% (Hawton et al, 1992;Kilmann et al, 1987;McCabe, 2001;Reynolds, Cohen, Schochet, Price, & Anderson, 1981;Sarwer & Durlak, 1997). This finding may be explained by the fact that during face-to-face therapy, the therapist has an opportunity within the session to address factors that may be inhibiting motivation to participate in treatment, such as ambivalence to change, lack of confidence in the treatment, or limited enthusiasm.…”
Section: Discussionmentioning
confidence: 88%
“…Attrition from Rekindle was much higher than has been reported for face-to-face psychological treatments for sexual dysfunction, where discontinuation rates have been found to range from between 1.6% and 52.6% (Hawton et al, 1992;Kilmann et al, 1987;McCabe, 2001;Reynolds, Cohen, Schochet, Price, & Anderson, 1981;Sarwer & Durlak, 1997). This finding may be explained by the fact that during face-to-face therapy, the therapist has an opportunity within the session to address factors that may be inhibiting motivation to participate in treatment, such as ambivalence to change, lack of confidence in the treatment, or limited enthusiasm.…”
Section: Discussionmentioning
confidence: 88%
“…Kilmann [17] studied the effects of three group treatment formats on 20 men with secondary ED. After a comprehensive medical and psychological screening, each couple was assigned to one of three treatment groups (communication technique training, sexual technique training, and combination treatment) or to one of two control groups (attention‐placebo, no‐treatment).…”
Section: Gt Vs Control Group (Waiting List No Treatment)mentioning
confidence: 99%
“…In a subgroup analysis comparing one study with men between 30 and 39 years old [24] to four studies with men at 45 years old and older [13,15,17,20], no statistical differences were identified.…”
Section: Gt Vs Control Group (Waiting List No Treatment)mentioning
confidence: 99%
“…A number of studies in the last 15 years have demonstrated that this is a disorder experienced by many men, particularly those over the age of 40 years [2,3]. Treatment for this disorder has varied over the past 50 years, with treatment in the 1970s and 1980s largely focusing on psychological interventions [4–6]. However, in the last 20 years the use of oral medications for ED has increased substantially, with treatments mainly adopting intracavernousal injection therapy [7] or more recently oral medications [8–10].…”
Section: Introductionmentioning
confidence: 99%